The international structure of a pala and a peat plateau in the Rivière Boniface region, Québec: Interferences on the formation of ice segregation mounds - Allard, Michel; Rousseau, Luc (Géographie physique et Quaternaire, 1999)
AbstratThe internal structure of a 5.7 m high palsa was studied through a pattern of closely spaced drill holes in permafrost along two orthogonal section lines. Holes were also drilled on a 1.3 m high peat plateau along a topographic transect for comparison purposes. The morphology of the palsa closely reflects the shape of the ice-rich core heaved by the growth of thick ice lenses in thick marine clay silts of the Tyrrell Sea. During and since palsa growth, the sand and peat covering was deformed by gelifluction and sliding and was also partly eroded by overland flow and wind. Palsa growth was accompanied by the formation of numerous ice-filled fault planes in the frozen sediments. The peat plateau was heaved to a lower height through the formation of thin ice lenses in an underlying layer of sandy silt only 1.4 m thick; this sediment is believed to be of intertidal origin. Therefore, the local Quaternary geomorphological settings are at the origin of differences in morphology and size between the palsa and the peat plateau. General inferences for the development of palsas and like landforms are made from the findings of the study.